Effect of using acid whey for marinating chicken breast muscles in organic production - Małgorzata Ormian, Anna Augustyńska-Prejsnar; Kluz, Maciej; Sokołowicz, Zofia (Emirates Journal of Food and Agriculture, 2019)
Currently, there is an increase in the group of consumers looking for poultry products obtained from the organic housing system, who pay attention to the relationship between diet and health. The research material consisted of breast muscles of organic chickens that were marinated for 24 hours with acid marinades: acid whey (n=30) and lemon juice (n=30). Acid whey was used in the study as a new ingredient in comparison to the traditional ingredient of marinades (lemon juice). The control group (n=30) were non-marinated breast muscles. The physicochemical parameters (marinade absorption, pH, Water Holding Capacity, colour L*a*b*, shear force, chemical composition) and microbiological (mesophilic aerobic bacteria, Pseudomonas spp., coli group, lactic acid bacteria) ones of breast muscles were evaluated immediately after marinating, as well as after grilling treatment. The sensory evaluation was also conducted. Raw breast muscles marinated using whey, in comparison with those marinated with lemon juice, were characterized by (p<0,05) a higher absorption of the marinade, lower saturation of the redness (a*), better tenderness measured by the shear force (N) and higher ash content. Also, after heat treatment, marinated breast muscles maintained a better (p<0,05) tenderness and juiciness and higher ash content. The study has shown that acid whey can be used as a new marinade in organic chicken meat marinades, as it causes a reduction in the redness saturation, higher ash content, improvement of tenderness and juiciness and increase in the microbiological safety of the product. The use of acid whey meets the expectations of consumers for the use of natural food additives that have a positive impact on human health.